2017
DOI: 10.1186/s12936-017-1848-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of climatic variability on malaria trends in Baringo County, Kenya

Abstract: BackgroundMalaria transmission in arid and semi-arid regions of Kenya such as Baringo County, is seasonal and often influenced by climatic factors. Unravelling the relationship between climate variables and malaria transmission dynamics is therefore instrumental in developing effective malaria control strategies. The main aim of this study was to describe the effects of variability of rainfall, maximum temperature and vegetation indices on seasonal trends of malaria in selected health facilities within Baringo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
39
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 40 publications
7
39
0
1
Order By: Relevance
“…Reproduction of P. vivax in mosquitoes takes 55 days at temperatures of 16 °C, 29 days at 18 °C, and only 7 days at 28 °C . In Baringo County, Kenya, between 2000 and 2014, higher rainfall at a lag of 2 months resulted in increased malaria transmission across all four climate zones . The same 2 months lag time was found in another study in South Africa .…”
Section: Climate Change and Infectious Diseasessupporting
confidence: 64%
“…Reproduction of P. vivax in mosquitoes takes 55 days at temperatures of 16 °C, 29 days at 18 °C, and only 7 days at 28 °C . In Baringo County, Kenya, between 2000 and 2014, higher rainfall at a lag of 2 months resulted in increased malaria transmission across all four climate zones . The same 2 months lag time was found in another study in South Africa .…”
Section: Climate Change and Infectious Diseasessupporting
confidence: 64%
“…We observed peak numbers of malaria cases in August, 3 months after the end of the rainy season, when temperatures increase to moderate levels. The clustering of malaria cases 2 to 3 months after periods of increased rainfall has been reported previously [22,23].…”
Section: Discussionmentioning
confidence: 66%
“…gambiae density and a 2-month lag in rainfall peak (Kristan et al, 2008). Similarly, a recent study in Baringo County reported a 2-month lag between increased malaria cases and rainfall across the four ecological zones (Kipruto et al, 2017).…”
Section: Discussionmentioning
confidence: 99%